2010
DOI: 10.1007/s11103-010-9673-9
|View full text |Cite
|
Sign up to set email alerts
|

Both the constitutive Cauliflower Mosaic Virus 35S and tissue-specific AGAMOUS enhancers activate transcription autonomously in Arabidopsis thaliana

Abstract: The expression of eukaryotic genes from their cognate promoters is often regulated by the action of transcriptional enhancer elements that function in an orientation-independent manner either locally or at a distance within a genome. This interactive nature often provokes unexpected interference within transgenes in plants, as reflected by misexpression of the introduced gene and undesired phenotypes in transgenic lines. To gain a better understanding of the mechanism underlying enhancer/promoter interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…5a), which is not surprising, since transcription initiation could have occurred at virtually any site within the 2-kb TBS fragment leading to the generation of non-functional transcripts. Several recent studies have shown that a wide variety of enhancers can initiate transcription autonomously in a range of organisms (Dobi and Winston 2007;Kim et al 2007;Ling et al 2005;Routledge and Proudfoot 2002;Tuan et al 1992;Singer et al 2010a), which raises the possibility that the observed GUS-specific transcripts initiated by the TBS element in this study result from the presence of a cryptic enhancer element within the full-length TBS fragment. Furthermore, since enhancers function in an orientation-independent manner (for example Banerji et al 1981), this enhancerinitiated transcription is likely bi-directional, which would correspond to the fact that transcription of a downstream reporter gene was observed when the TBS was in either orientation, but at a seemingly higher level in the reverse orientation (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…5a), which is not surprising, since transcription initiation could have occurred at virtually any site within the 2-kb TBS fragment leading to the generation of non-functional transcripts. Several recent studies have shown that a wide variety of enhancers can initiate transcription autonomously in a range of organisms (Dobi and Winston 2007;Kim et al 2007;Ling et al 2005;Routledge and Proudfoot 2002;Tuan et al 1992;Singer et al 2010a), which raises the possibility that the observed GUS-specific transcripts initiated by the TBS element in this study result from the presence of a cryptic enhancer element within the full-length TBS fragment. Furthermore, since enhancers function in an orientation-independent manner (for example Banerji et al 1981), this enhancerinitiated transcription is likely bi-directional, which would correspond to the fact that transcription of a downstream reporter gene was observed when the TBS was in either orientation, but at a seemingly higher level in the reverse orientation (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Conversely, long-range activation appears to involve transcription initiation at both the enhancer and target promoter. This long-range transcriptional activation resembles the scanning-based mechanisms often seen in animals, such as facilitated tracking, whereby RNA polymerase II and a bound enhancer track along the DNA from enhancer to target promoter to ultimately form a loop (Singer et al 2010a). The migration of RNA polymerase II along the intervening DNA, and the consequential synthesis of intergenic RNA, has been proposed to supply enhancer-bound proteins to the target promoter and/or 'open' the nucleosomal structure of the associated DNA through the action of histone acetyltransferases (Zhu et al 2007).…”
Section: Introductionmentioning
confidence: 82%
“…As enhancer-blocking insulators function solely when situated between an enhancer and promoter, the orientation of a compound insulator-enhancer element in which the insulator was proximal to the target promoter would theoretically block both internal and external enhancers, while a reversed orientation would block the external enhancer but not that included within the element itself (reviewed by West et al 2002). Intriguingly, the TBS element has been found to initiate transcription of a downstream reporter gene autonomously (Singer et al 2011b), which seems to be characteristic of enhancers in artificial systems within plant species (Singer et al 2010a) and raises the possibility that the TBS fragment is a composite element containing an internal enhancer upstream of the insulator, which could explain its polarity.…”
Section: Enhancer-blocking Insulators In Transgenic Plantsmentioning
confidence: 99%
“…The CaMV 35S enhancer can change the transcription initiation site in the promoter of the reporter gene and also its specificity (Singer et al 2010a). In our experiments the PtrCOMT2 promoter specificity was observed to change when the 35S enhancer was inserted either in front or behind the 2 kb PtrCOMT2 promoter, but did not change the specificity of the 3.3 kb promoter.…”
Section: Discussionmentioning
confidence: 99%